2021
DOI: 10.1093/rheumatology/keab578
|View full text |Cite
|
Sign up to set email alerts
|

Calcium pyrophosphate crystal deposition in a cohort of 57 patients with Gitelman syndrome

Abstract: Objective Gitelman syndrome (GS) is the most frequent salt-wasting genetic tubulopathy and a source of hypokalaemia and hypomagnesemia. Chondrocalcinosis (CC) is a frequent feature of GS. The aim of our study was to determine the prevalence, distribution patterns, clinical phenotypes and risk factors of CC in GS. Methods This prospective study of a cohort of 57 patients with GS included a systematic screening for CC by periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Next, in order of decreasing frequency, were the wrist, at 50.9%, the ankle, at 38.6%, the temporomandibular (TM) joint, at 36.4%, the shoulder, at 33.3%, the hip, at 22.8%, the elbow, at 14.0% and the sclera/choroid, at 12.1%. Both age and hypomagnesaemia were independent factors found to be associated with CC in GS [12]. This is a thorough analysis of CC in GS illustrating preferential involvement at the cervical spine and knees.…”
Section: Clinical Observationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Next, in order of decreasing frequency, were the wrist, at 50.9%, the ankle, at 38.6%, the temporomandibular (TM) joint, at 36.4%, the shoulder, at 33.3%, the hip, at 22.8%, the elbow, at 14.0% and the sclera/choroid, at 12.1%. Both age and hypomagnesaemia were independent factors found to be associated with CC in GS [12]. This is a thorough analysis of CC in GS illustrating preferential involvement at the cervical spine and knees.…”
Section: Clinical Observationsmentioning
confidence: 78%
“…There is a wellrecognised association between GS and CC and various small studies and case series have depicted a propensity of CC to manifest at the knee, symphysis pubis and shoulder [11]. In this cross-sectional prospective study, Chotard et al sought to determine the prevalence, clinical phenotypes, distribution patterns and risk factors for CC in individuals with GS [12]. A cohort of 57 patients with GS were identified and they underwent a systematic screening for CC.…”
Section: Clinical Observationsmentioning
confidence: 99%
“…A notable aspect of this article is that the patient underwent a PET-CT scan to confirm the site of infection, and the PET-CT revealed a hypermetabolic area at the odontoid process level. Previous studies have typically reported CT imaging alone for diagnosis ( 9 , 22 , 23 ). Only Monet has reported PET-CT images of CDS accompanied by polymyalgia rheumatica ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Chotard et al, 79% of patients with Gitelman’s Syndrome had evidence of chondrocalcinosis at least at one site, with the highest prevalence at the cervical spine (81.8%) followed by the knee (52.6%) and the wrist (50.9%). 30 In a patient with newly diagnosed acute CPP arthritis, particularly in those of younger age, evaluation should include measurement of serum calcium, ferritin, magnesium, phosphorus, alkaline phosphatase, and thyroid-stimulating hormone.…”
Section: Clinical Phenotypes Of Cppdmentioning
confidence: 99%